Synthesis, characterizations and electro-optical properties of nonlinear optical polyimide/silica hybrid (eXPRESS Polymer Letters)
Transparent Nonlinear Optical (NLO) inorganic/organic (polyimide/silica) hybrid composites with covalent links between the inorganic and the organic networks were prepared by the sol-gel method. The silica content in the hybrid films was varied from 0 to 22.5/wt%. The prepared PI hybrids were characterized by IR, UV-Vis, Thermogravimetric analysis (TGA), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). They exhibited fair good optical transparency. The SiO2 phase was well dispersed in the polymer matrix. DSC and TGA results showed that these hybrid materials had excellent thermal stability. The polymer solutions could be spin coated on the indium-tin-oxide (ITO) glass to form optical quality thin films. The electro-optic coefficients (γ33) at the wavelength of 832 nm for polymer thin films poled were in the range of 19-27 pm/V.